Ethics in action [videorecording] - Haynes, Robert; Walters, Thomas (Calif. Brooks/Cole Pub., 1998)
Focuses on the basic elements of ethical decision making, how the counselor values influence the helping relationship with clients and the importance of defining appropriate boundaries in work with clients.
VHS.
Narration, Annie Hansen.
Keywords: Situational ethics; Social problems; Counseling; ETHICS; PSYCHOLOGY